KAJIAN PENGARUH JUMLAH DAN LEBAR PERKUATAN GEOTEKSTIL TERHADAP DAYA DUKUNG TANAH GAMBUT - Martini Martini; Fathuddin Al-Anshori (Jurusan Teknik Sipil Universitas Tadulako, 2015)
Peat soils have a high compressibily and low bearing capacity. These unfavorable characteristics can cause differential settlement and the construction failure, so that the appropriate improvement methods are required to solve the problems. Peat soil improvement methods that commonly used are mechanical and chemical improvement methods. In this research, the peat soil reinforced with geotextile was conducted in order to find the influence of the reinforcement in increasing the bearing capacity. Reinforcement was applied to the construction model with variation in the number of reinforcement which were N=1, N=2, N=3, and reinforcement width which were 2B, 3B and 4B (B is foundation width in scale). The results show that the insertion of geotextile sheets in peat soil can increase the bearing capacity of the soil foundation. The increasing of the bearing capacity is proportional to the increasing of the number and width of the geotextile. Variation in reinforcement width is given more influence in increasing the ultimate bearing capacity (q) compare to variation in the number of reinforcement. Compare to the modeled construction without reinforcement, the maximum bearing capacity increase as much as 232.3 % and BCR as of 3.32 with reinforcement width of 4B and N=3.Key words: peat, reinforcement, bearing capacity